Implementation Isomorphic JavaScript Applications - Quintana-Cruz, Hernán Alejandro (2015)
With the evolution of browsers and the implementation of new Web standards (HTML5), new tools became available that have enabled us to create more complex web applications with better user experiences. Over time, these types of applications have proven useful, but deteriorate the user experience as extended lengths of time are used load the data on each page. For this same reason, it is proven that there is a need for interaction from the server to the generation page with the hybrid applications. One such technique was to allow the use (creation and modification) of graphical user interface elements, both in the client just like the server, which is why these applications are called isomorphic. This article shows the process that was undertaken to arrive at the concept of isomorphic applications, which describes the characteristics that must have an isomorphic implementation and, finally, presents a model of application architecture with code examples.